The Impact of Internship Experience and Soft Skills on Work Readiness: The Mediating Role of Self-Efficacy Among Management Students at Padang State University - Yudha Ahmad Ramdhani; Mia Ayu Gusti (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
Work readiness has become an important issue in higher education due to the increasing gap between academic competencies and labor market expectations. Practical experience, interpersonal competence, and psychological readiness are considered essential factors in preparing graduates to enter professional environments successfully. Internship experience enables students to gain direct exposure to workplace situations and apply theoretical knowledge in practical contexts, while soft skills strengthen communication, teamwork, adaptability, and problem-solving abilities. In addition, self-efficacy plays a critical role in shaping students’ confidence in dealing with work-related challenges. Using a quantitative explanatory approach, data were collected from 160 final-year students and fresh graduates of the Management Program at Padang State University who had participated in internship programs. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS software. The findings indicate that internship experience and soft skills positively and significantly affect both self-efficacy and work readiness. Self-efficacy also demonstrates a significant positive influence on work readiness and partially mediates the relationships between internship experience, soft skills, and work readiness. These findings emphasize the importance of integrating experiential learning, soft skills development, and psychological empowerment into higher education strategies to improve graduate employability and career preparedness.